Theological Implications of Land Disputes in Indonesia: A Justice Perspective from Christian and Indigenous Theologies (Indonesian Theological Justice Review, 2025)
Land disputes in Indonesia, particularly involving indigenous communities and corporate interests, have become a pressing issue for justice and human rights. This paper analyzes how Christian and Indigenous theological perspectives contribute to understanding and addressing land rights and justice in the context of these disputes. Christian theology’s teachings on stewardship, human dignity, and the moral obligation to protect the land are explored in relation to current land struggles, especially those that affect indigenous communities in areas like Kalimantan and Papua. Indigenous theological frameworks, which often include a deep spiritual connection to land, are also examined in the context of land justice. The paper discusses how indigenous communities view land as a sacred trust and how their traditional legal systems intersect with state and corporate policies. Furthermore, the paper highlights the role of religious leaders and organizations in advocating for land rights, supporting legal challenges to land grabs, and promoting environmental justice. The research concludes with policy recommendations, including the need for greater recognition of indigenous land rights within both religious and legal frameworks to ensure that justice is served for communities at risk of displacement.